PENGARUH KOMPENSASI TERHADAP KINERJA PEGAWAI PADA KANTOR CAMAT LUAHAGUNDRE MANIAMOLO - Ferlin Fau (Jurnal Ilmiah Mahasiswa Nias Selatan, 2024)
The purpose of this research is to determine the effect of compensation on employee performance at the Luahagundre Maniamolo District Head Office. This research is quantitative research, with a survey research type where all data is obtained through observation, questionnaires and documentation. This research uses a simple linear regression technique. The sample used in this research was 30 respondents. Based on the research results, the compensation variable (X) affects employee performance (Y) at the Luahagundre Maniamolo District Head Office using a simple linear regression technique. The results of the research after the data were processed with SPSS.21 show that there is a positive influence between compensation variables on employee performance variables, which can be determined through a simple regression equation, namely Y=36.581+0.0515In this study it can be concluded that, the constant value (a) is 36,581, meaning that if the compensation value (X) is zero, then the employee performance results (Y) at the Luahagundre Maniamolo sub-district office are positive, namely 0.515 and the more the compensation value is increased, the employee performance results (Y) at the Luahagundre Maniamolo District Head Office will also increase. Luahagundre Maniamolo District Head Office shows that the R Square determinant value resulting from statistical data analysis shows 0.135 or 13.5%. This means that compensation (X) influences employee performance (Y) at Luahagundre Maniamolo District Head Office 13.5%. obtained was 86.5% which was influenced by other variables not mentioned in this research.